1996
DOI: 10.2307/2138080
|View full text |Cite
|
Sign up to set email alerts
|

"Induction of Abortion with Mifepristone (RU 486) and Oral or Vaginal Misoprostol."

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…21 However, it has been reported that women preferred oral administration and valued having additional choice. 22 Sublingual administration avoids the first-pass effect through the liver associated with oral administration and the inconvenience and intrusion of vaginal administration.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, it has been reported that women preferred oral administration and valued having additional choice. 22 Sublingual administration avoids the first-pass effect through the liver associated with oral administration and the inconvenience and intrusion of vaginal administration.…”
Section: Discussionmentioning
confidence: 99%
“…Women in the expectant management arm were allowed home with no intervention. In the medical management arm, women with an incomplete miscarriage were admitted to hospital and given a single vaginal dose of 800 μg misoprostol 19 20. Women with early fetal or embryonic demise were pre-treated with a single oral dose of 200 mg mifepristone,21 then admitted to hospital 24-48 hours later for a single vaginal dose of 800 μg misoprostol.…”
Section: Methodsmentioning
confidence: 99%
“…92-98% (8,9,17,18) and 600 mg i.e. 87-97% (19,20), demonstrating the potential efficacy of 100 mg mifepristone for medical abortion. Efficacy of low dose mifepristone was also reported by Jerbi et al (13).…”
Section: Discussionmentioning
confidence: 98%